First‐line treatment of 102 chronic myeloid leukemia patients with imatinib: A long‐term single institution analysis. Issue 10 (31st July 2014) - Viganò, Ilaria; Di Giacomo, Nunzio; Bozzani, Sofia; Antolini, Laura; Piazza, Rocco; Gambacorti Passerini, Carlo
<x xml:space="preserve">Abstract</x> Imatinib mesylate radically changed the natural history of chronic myeloid leukemia (CML). The recent availability of alternative tyrosine kinase inhibitors (TKIs) renders the clinical management of CML more complex. In this article, we summarize our long‐term single institution experience. From 2003 to 2012, 102 patients with newly diagnosed chronic phase CML were referred to our institution and treated with imatinib mesylate as first‐line therapy. All patients were followed inside a dedicated CML clinic. At 1 year, 82/95 patients (86.3%) achieved complete cytogenetic response (CCyR) using a treatment performed analysis (TPA); when using an intention to treat analysis, 85/102 patients (83.3%) obtained CCyR. At 3 months, 58 patients (64.4% TPA) obtained a BCR‐ABL transcripts level <10%. A major molecular response (MMR) was obtained by 38% and 53% of patients at 1 and 2 years. Twenty patients (19.6%) discontinued treatment with imatinib; six of them did so in the initial 2 years of treatment (4 for resistance and 2 for adverse events). We observed seven deaths (6.86%). Overall survival (OS) at 6 years is 95.1% (95% C.I. 90–100%) and is not different from that of the general population. No patient experienced progression of disease (95% C.I.: 0–3%). Our results suggest that patient management is a crucial point to obtain a successful therapeutic outcome: at 1 year CCyR and MMR rates are similar to the results obtained with second generation TKIs and OS is not different from that of the general population.Am. J. Hematol. 89:E184–E187, 2014. © 2014 Wiley Periodicals, Inc.